DESAIN ALAT PENGEBOR TANAH UNTUK MEMBUAT LUBANG TANAM TANAMAN TAHUNAN - Frans Jusuf Daywin; Lia Antik Kurniawati; Ika Widiastuti (Jurnal Keteknikan Pertanian, 2007)
ABSTRACT Making hole for planting perennial crops in Indonesia, especially in the farmer's plantation is still dominated by simple equipment such as hoe, manual drill etc,. while using heavy equipment such as post-hole-digger is performed only by big estates. For this reason, it is necessary to design soil-hale-digger machine which suits the field condition in Indonesia. The design was bused on Pahl and Beitz  method which optimizing the use of meterial, technology and economic condition and consist of severeral stops, namely, classification of the tasks, conceptual design, embodiment design and detail design. Structural design of the post-hole-digger consisted of several main components, namely, source of power. power delivery. power transmission system, point of drill and edge of point. Source of power used was a two-stroke gasoline engine of 2.38 kW delivered through a centrifugal clutch and transmitted by worm gear with 10 : 1ratio. Keywords: design, soil-hale-digger, planting, perennial crops Diterima: 8 Mei 2007; Disetujui: 22 Oktober 2007